IMPLEMENTASI PEMBELAJARAN VOCABULARY BERBASIS TAKSONOMI BLOOM PADA ANAK SEKOLAH DASAR (KKN KELURAHAN BUMI AYU: PERUMAHAN ROYAL RESIDENCE 02 RT 29) - Azzahra, Novrida; Khairullah, M. Al Hafidz; Priska Azhari, Vegy; safitri, Nadia; Didayani, Cici (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Vocabulary mastery is a fundamental skill that is crucial for advancing English language proficiency among elementary school children. However, the process of learning vocabulary in the community is still hampered by various issues, such as a lack of interactive teaching methods and limited opportunities for students to apply vocabulary in real-life situations. This community service project aims to improve English vocabulary mastery through the application of Bloom’s Taxonomy-based learning using the Asset-Based Community Development (ABCD) approach. The activities were conducted at Al-Hidayah Mosque, Royal Residence 02 Housing Complex, RT 29, Bumi Ayu Village, Bengkulu City, with a focus on elementary school students. The implementation method was carried out in stages through the six cognitive levels of Bloom’s Taxonomy—remembering, understanding, applying, analyzing, evaluating, and creating—which were integrated into various learning activities such as the use of visual media, flashcards, educational games, quizzes, discussions, and practical exercises using vocabulary based on the themes “Exploring Animals at the Zoo,” “Parts of the Human Body,” Places and Buildings, and Numbers, Days, Months, and Time. The results of the study indicate that learning based on Bloom’s Taxonomy is effective in improving students’ vocabulary mastery, in terms of recognizing, understanding, and using vocabulary in simple communication. In addition, the ABCD approach successfully maximized community resources with the support of neighborhood leaders, parents, and the use of the Al-Hidayah Mosque as a learning center, resulting in a learning process that was active, participatory, and sustainable. Thus, the implementation of vocabulary learning based on Bloom’s Taxonomy through the ABCD approach can be an effective solution for improving English vocabulary mastery while gradually developing students’ thinking skills through community service activities